THE PLACE OF FINANCIAL INSTRUMENTS IN THE INTELLECTUAL CAPITAL MANAGEMENT SYSTEM OF AN ENTERPRISE - Оксана Сторожук; Володимир Мельник; Оксана Синюк; Оксана Нагірна; Олена Халіна; Богдан Колядко (Фінансово-кредитна діяльність: проблеми теорії та практики, 2025)
The article examines the place and role of financial instruments in the intellectual capital management system at a modern industrial enterprise in the conditions of the transformational economy of Ukraine. The aim is to attempt to assess the impact of financial instruments on the system of managerial decision-making regarding the development of intellectual capital using the example of modern industrial enterprises of Ukraine, as well as to identify the most effective of them in the context of supporting the knowledge component of the economy. Based on theoretical principles and analysis of empirical data, a full-fledged multifactor correlation regression study was conducted. As part of the study, a system of dependent variables was formed that represent key aspects of the intellectual capital of the enterprise: R&D costs, the number of implemented innovations, the level of automation, the number of employees with higher education and investments in personnel training. The results of the analysis showed that the greatest positive impact on intellectual capital is exerted by tax benefits, state support and foreign direct investment. Instead, bank lending and leasing have a less pronounced or indirect effect.